Financial distress and competitors' investment - Garcia-Appendini, Emilia (Journal of Corporate Finance, 2018)
This paper analyzes whether the financial distress of a firm affects the investment decisions of non-distressed competitors. On average, firms in distress impose indirect costs to non-distressed competitors by increasing costs of credit in the industry and hence restricting credit access and investment. These average negative effects continue to hold in the absence of industry downturns and are temporary. However, negative effects are mitigated for firms with stronger balance sheets or in concentrated markets, suggesting that firms with strong balance sheets prey on their weaker rivals to improve their market position.